PENGARUH PENERAPAN TEKNOLOGI INFORMASI DAN PROFESIONALISME TERHADAP KINERJA AUDITOR - Rindy Wulandari; Eka Rima Prasetya (EkoPreneur, 2019)
The purpose of this study to determine the effect of the application of information technology and professionalism on auditor performance. The independent variables in this study are information technology and professionalism and auditor performance as the dependent variable. The population in this study were auditors who worked at the Public Accounting Firm (KAP) in the area of West Jakarta, amounting to 35 auditors. The data used in this study are primary data. The technique used in data collection is the survey technique by distributing questionnaires to auditors. Data analysis was performed using multiple linear regression methods and hypothesis testing with t test and F test. The conclusions of the study show that: 1) Information Technology influences Auditor Performance; 2) Professionalism influences Auditor Performance; 3) Simultaneous application of Information Technology and Professionalism influences Auditor Performance. Keywords: Information Technology, Professionalism, Auditor Performance